Perovskite film, preparation method thereof and perovskite solar cell

By using cationic surfactant to reduce surface tension during the film formation process of perovskite film, the problem of pore-like defects during the film formation process of perovskite film is solved, and the smooth and denseness and performance of perovskite film are achieved. promote.

CN119451521APending Publication Date: 2025-02-14GUANGDONG BILIGHT INTELLIGENT MANUFACTURING TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411738974.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The perovskite film synthesized by water system is prone to appear pores during the film formation process, which affects its performance.

Method used

The cationic surfactant is introduced into the divalent inorganic saline aqueous solution to reduce the surface tension of the solution, optimize the nucleation-growth process, reduce pinhole-like morphological defects, and obtain a smooth and dense perovskite film.

Benefits of technology

By reducing charge trap density and extending carrier lifetime, the performance of perovskite films is significantly improved, making them more suitable for solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451521A_ABST
    Figure CN119451521A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cell materials, in particular to a perovskite film, a preparation method thereof and a perovskite solar cell. The preparation method of the perovskite film comprises the steps that a divalent inorganic salt aqueous solution is prepared, divalent inorganic salt in the divalent inorganic salt aqueous solution is inorganic salt corresponding to perovskite divalent cations, and the divalent inorganic salt aqueous solution contains a cationic surface active agent; performing film-forming treatment on the divalent inorganic salt aqueous solution to obtain a divalent inorganic salt film; and converting the divalent inorganic salt in the divalent inorganic salt film into organic-inorganic hybrid perovskite to obtain the perovskite film. Based on the action of the cationic surface active agent, the surface tension of the divalent inorganic salt aqueous solution is reduced, spreading is easy in the film forming process, nucleation-growth of the divalent inorganic salt is optimized, the pinhole generation risk of the divalent inorganic salt film is reduced, and finally the smooth and compact perovskite film can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of solar cell materials, and in particular relates to a perovskite film and a preparation method thereof, and a perovskite solar cell. Background Art

[0002] Perovskite materials are a type of semiconductor materials with uniform size and high color purity. Their elemental composition has a crystal structure similar to that of the mineral CaTiO3, and they are a promising photovoltaic material. Perovskite materials have strong light absorption capacity and a wide absorption range, and have great advantages in the field of optoelectronics. For example, perovskite solar cells (PSCs) with perovskite materials as light-absorbing layers have developed rapidly. They have excellent carrier mobility, high absorption coefficient, and low-cost solution processing, and have attracted widespread attention from the business community.

[0003] The solution-based synthesis of perovskites has a good power conversion efficiency (PCE). However, the aprotic polar solvents used to prepare perovskites, such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP), are usually skin penetrating and carcinogenic. The toxicity of these solvents in the perovskite production process can adversely affect the health of manufacturing workers, hinder industrial production, and bring environmental pollution risks. Therefore, from the perspective of green chemistry, the preparation of perovskites by aqueous synthesis has been applied.

[0004] At present, the method of synthesizing perovskite in water system is: after the divalent inorganic salt aqueous solution system is made into a divalent inorganic salt film, it is converted into an organic-inorganic hybrid perovskite through a solid-liquid reaction system. However, in this process, the divalent inorganic salt aqueous solution generally has a high surface tension, and it is easy to have pores after film formation, thus affecting the performance of the perovskite film after the final conversion. Summary of the invention

[0005] The purpose of this application is to provide a perovskite film and a preparation method thereof, and a perovskite solar cell, aiming to solve the technical problem of how to make the perovskite film denser to improve its performance.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a method for preparing a perovskite film, comprising:

[0008] preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of perovskite, and the divalent inorganic salt aqueous solution contains a cationic surfactant;

[0009] subjecting the divalent inorganic salt aqueous solution to a film-forming treatment to obtain a divalent inorganic salt film;

[0010] The divalent inorganic salt in the divalent inorganic salt film is converted into an organic-inorganic hybrid perovskite to obtain a perovskite film.

[0011] In some embodiments, the cationic surfactant has the following general chemical formula:

[0012]

[0013] Wherein, R1 and R2 are straight-chain alkyl groups of 1 to 3 carbon atoms, R3 and R4 are straight-chain alkyl groups of 10 to 20 carbon atoms, and X is a halogen atom.

[0014] In some embodiments, the surfactant includes at least one of dimethyldioctadecylammonium iodide, dimethyldioctadecylammonium bromide, and dimethyldioctadecylammonium chloride.

[0015] In some embodiments, in the divalent inorganic salt aqueous solution, the concentration of the divalent inorganic salt is 1.0-2.0 mol / L, and the concentration of the cationic surfactant is 2-8 mg / mL.

[0016] In some embodiments, the step of subjecting the divalent inorganic salt aqueous solution to film-forming treatment includes: coating the divalent inorganic salt aqueous solution to film-forming treatment under the conditions of relative humidity <10% and temperature <20° C., and then performing a drying treatment.

[0017] In some embodiments, the drying process is performed at a temperature of 80 to 100° C. and for a time of 20 to 40 minutes.

[0018] In some embodiments, the step of converting the divalent inorganic salt in the divalent inorganic salt film into an organic-inorganic hybrid perovskite includes: first placing the divalent inorganic salt film in a methylammonium halide solution for multiple immersion treatments, and after drying, spin coating a solution containing a formamidinium halide salt for annealing to obtain a formamidinium-based organic-inorganic hybrid perovskite.

[0019] In some embodiments, the methylammonium halide solution contains methylammonium iodide and methylammonium chloride dissolved in a molar ratio of (3.5-4.5):1;

[0020] And / or, the solution containing formamidine halide salt contains formamidine iodide and methylammonium iodide dissolved in a molar ratio of (7-10):1;

[0021] And / or, the soaking treatment time is 4 to 5 minutes each time;

[0022] And / or, the annealing treatment time is 140-160°C.

[0023] In a second aspect, the present application provides a perovskite film prepared by the preparation method provided in the first aspect of the present application.

[0024] In a third aspect, the present application provides a perovskite solar cell, comprising the perovskite film provided in the second aspect of the present application.

[0025] The first aspect of the present application provides a method for preparing a perovskite film, in which a cationic surfactant is added to a prepared divalent inorganic salt aqueous solution. Based on the action of the cationic surfactant, the surface tension of the divalent inorganic salt aqueous solution is reduced, and the film-forming process is easy to spread, thereby optimizing the nucleation-growth of the divalent inorganic salt, and significantly reducing the risk of pinhole formation in the divalent inorganic salt film, and finally a smooth and dense perovskite film can be obtained. The perovskite film prepared in this way has a lower charge trap density and a longer carrier lifetime, and can be well used in solar cells.

[0026] The perovskite film provided in the second aspect of the present application is prepared by the preparation method provided in the first aspect of the embodiment of the present application. Therefore, the perovskite film of the present application is smooth and dense as a whole, has a lower charge trap density and a longer carrier lifetime, and can be well used in solar cells.

[0027] The perovskite solar cell provided in the third aspect of the present application includes the perovskite film provided in the second aspect of the present application. Based on the advantages of the perovskite film, the perovskite solar cell of the present application has good conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0029] Figure 1 This is a relationship diagram of the effect of the concentration of a cationic surfactant on the surface tension of an aqueous solution in an embodiment of the present application;

[0030] Figure 2 This is a comparison diagram of the microscopic effects of a cationic surfactant on a perovskite film in a method for preparing a perovskite film according to an embodiment of the present application;

[0031] Figure 3 is a comparative spectrum of fluorescence photoluminescence of the perovskite film obtained by the preparation method of the perovskite film of the embodiment of the present application; (a) is a steady-state fluorescence photoluminescence spectrum, (b) is a transient fluorescence photoluminescence spectrum; wherein, with C 38 H 80ClN represents the perovskite film curve of Example 1, w / o C 38 H 80 ClN represents the perovskite film curve of Comparative Example 1;

[0032] Figure 4 is a comparison diagram of the photovoltaic efficiency of the perovskite film obtained by the preparation method of the perovskite film of the embodiment of the present application for use in solar cells; wherein, with C 38 H 80 ClN represents the perovskite film solar cell curve of Example 1, w / oC 38 H 80 ClN represents the perovskite film solar cell curve of comparative example 1. DETAILED DESCRIPTION

[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0035] In the present application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.

[0036] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0039] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0040] The photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has been significantly improved. From the perspective of green chemistry, the use of water solvents to synthesize materials is the most ideal and environmentally friendly. Therefore, the use of divalent inorganic salt aqueous solutions to prepare perovskites has been well applied. However, the aqueous perovskite process has the following difficulties: Compared with organic solvents (such as DMF), water has a higher surface tension (72.8mN / m), and aqueous divalent inorganic salts that form films are prone to cracked "island-like" morphology. At present, most aqueous perovskites have pinhole-like morphology defects on their surfaces, which aggravate the surface charge recombination, so the efficiency of aqueous perovskites is relatively low.

[0041] Based on this, the embodiment of the present application introduces a cationic surfactant to promote the spreading of a divalent inorganic salt aqueous solution and reduce the surface tension of the solution, thereby optimizing the nucleation-growth of the divalent inorganic salt, and finally obtaining a smooth and dense perovskite film. The cationic surfactant has an excellent ability to regulate the crystallization of perovskite, which can greatly improve the efficiency of the perovskite film in the device. The specific technical solution is as follows.

[0042] In a first aspect, an embodiment of the present application provides a method for preparing a perovskite film. Specifically, the method for preparing a perovskite film of an embodiment of the present application includes:

[0043] S01: preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite, and the divalent inorganic salt aqueous solution contains a cationic surfactant;

[0044] S02: subjecting the divalent inorganic salt aqueous solution to a film-forming treatment to obtain a divalent inorganic salt film;

[0045] S03: Converting the divalent inorganic salt in the divalent inorganic salt film into an organic-inorganic hybrid perovskite to obtain a perovskite film.

[0046] The embodiments of the present application are based on the effect of cationic surfactants to reduce the surface tension of the divalent inorganic salt aqueous solution, so that the film-forming process is easy to spread, thereby optimizing the nucleation-growth of the divalent inorganic salt, and significantly reducing the risk of pinhole formation in the divalent inorganic salt film, and finally a smooth and dense perovskite film can be obtained.

[0047] In step S01, the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of the perovskite. For example, the chemical formula of the organic-inorganic hybrid perovskite material can be ABX3; wherein A is a monovalent organic cation, which can include CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), B is a divalent metal cation, specifically Pb 2+ Sn 2+ At least one of; X is a monovalent anion, specifically a halogen ion, including Cl - Br - and I - At least one of the following. The divalent inorganic salt is the soluble inorganic salt corresponding to B.

[0048] Taking the example that the divalent metal ions in the organic-inorganic hybrid perovskite can be lead ions or tin ions, the corresponding divalent inorganic salts can be lead salts or tin salts. Specifically, they can be the corresponding acetates or nitrates, for example, the lead salt can be lead nitrate or lead acetate, and the tin salt can be tin nitrate or tin acetate.

[0049] The preparation steps of the divalent inorganic salt aqueous solution may be: adding a divalent inorganic salt and a cationic surfactant into water and dissolving them to obtain the divalent inorganic salt aqueous solution.

[0050] In some embodiments, in the divalent inorganic salt aqueous solution, the concentration of the divalent inorganic salt is 1.0-2.0 mol / L, and the concentration of the cationic surfactant is 2-8 mg / mL. The divalent inorganic salt and the cationic surfactant of the above concentrations are added to water and dissolved to obtain a divalent inorganic salt aqueous solution, wherein the cationic surfactant can well reduce the surface tension of the divalent inorganic salt aqueous solution.

[0051] In some embodiments, the cationic surfactant has the following general chemical formula:

[0052]

[0053] Wherein, R1 and R2 are straight-chain alkyl groups of 1 to 3 carbon atoms, R3 and R4 are straight-chain alkyl groups of 10 to 20 carbon atoms, and X is a halogen atom.

[0054] The cationic surfactant with a double carbon long chain structure is a quaternary ammonium salt surfactant, which can be introduced into a divalent inorganic salt aqueous solution to effectively reduce the surface tension of the solution. At the same time, it can also passivate the perovskite defects well and form a moisture-proof layer on the surface of the organic-inorganic hybrid perovskite to enhance stability.

[0055] In some embodiments, the surfactant includes dimethyldioctadecyl ammonium iodide (C 38 H 80 IN), dimethyl dioctadecyl ammonium bromide (C 38 H 80 BrN), dimethyldioctadecyl ammonium chloride (C 38 H 80 Taking the cationic surfactant dimethyl di(octadecyl) ammonium chloride dissolved in deionized water as an example, Figure 1 As shown in the figure, the functional relationship between the surface tension of water and the concentration of dimethyldi(octadecyl)ammonium chloride added shows that its addition to deionized water can significantly reduce the surface tension of water (from 72mN / m to 25mN / m), and the critical micelle concentration (CMC) is 0.3mg / mL, which indicates that the cationic surfactant can effectively reduce the surface tension of the aqueous solution.

[0056] Step S02 is a divalent inorganic salt aqueous solution film forming process. In some embodiments, the divalent inorganic salt aqueous solution film forming treatment step includes: coating the divalent inorganic salt aqueous solution into a film under the conditions of relative humidity <10% and temperature <20°C, and then drying.

[0057] In an embodiment of the present application, the above-mentioned environmental humidity and temperature are controlled during the coating (e.g., spin coating) process to promote the spreading of the aqueous divalent inorganic salt solution on the surface of the substrate (e.g., the electron transport layer of the perovskite solar cell). Through the synergistic effect of "reducing surface tension" and "optimizing spreading dynamics", the easily broken island-shaped divalent inorganic salt can be transformed into a relatively continuous and compact divalent inorganic salt film.

[0058] In some embodiments, the temperature of the divalent inorganic salt aqueous solution after coating is 80-100° C. and the time is 20-40 minutes. Under the above conditions, the aqueous solvent can be dried well.

[0059] Step S03 is an organic-inorganic hybrid perovskite generation step.

[0060] In some embodiments, the step of converting the divalent inorganic salt in the divalent inorganic salt film into an organic-inorganic hybrid perovskite includes: first placing the divalent inorganic salt film in a methylammonium halide solution for multiple soaking treatments, drying, and then spin-coating a solution containing a formamidine halide salt for annealing to obtain a formamidine-based organic-inorganic hybrid perovskite. In this process, the divalent inorganic salt film can be first converted into a methylamine-based perovskite by soaking, and then converted into a formamidine-based organic-inorganic hybrid perovskite by exchanging monovalent ions, and the required formamidine-based organic-inorganic hybrid perovskite can be obtained according to the ratio of monovalent cations in the solution containing the formamidine halide salt, for example, it can be a formamidine-methylamine-based (different stoichiometric ratio) organic-inorganic hybrid perovskite.

[0061] In some embodiments, each soaking treatment lasts for 4 to 5 minutes; specifically, the soaking can be performed 3 to 4 times. After each soaking for 4 to 5 minutes, nitrogen is blown dry; through multiple soaking treatments, methylamine perovskite can be fully converted.

[0062] In some embodiments, the annealing treatment time is 140-160° C. Under this condition, the methylamine-based perovskite can be fully converted into the organic-inorganic hybrid perovskite of the methylamidine-based perovskite.

[0063] Specifically, the methylammonium halide solution contains methylammonium iodide (MAI) and methylammonium chloride (MACl) in a molar ratio of (3.5-4.5):1; the solution containing formamidinium halide contains formamidinium iodide (FAI) and methylammonium iodide (MAI) in a molar ratio of (7-10):1, and the finally obtained formamidinium-based organic-inorganic hybrid perovskite can contain both formamidinium-based and methylamine-based organic-inorganic hybrid perovskites. Furthermore, methylammonium chloride (MACl) is also dissolved in the solution containing formamidinium halide. In the methylammonium halide solution and the solution containing formamidinium halide, the solvent can be an alcohol solvent, such as isopropyl alcohol (IPA).

[0064] Furthermore, a passivation agent may be spin-coated on the surface of the perovskite film. For example, a passivation agent solution (the passivation agent is phenylethylamine iodide PEAI, the solvent is isopropanol, and the concentration is 4-6 mg / mL) is spin-coated on the surface of the perovskite film, and then dried to remove the solvent.

[0065] In the second aspect, the embodiment of the present application provides a perovskite film. That is, the perovskite film of the embodiment of the present application is prepared by the preparation method provided by the first aspect of the embodiment of the present application. The perovskite film of the embodiment of the present application is smooth and dense as a whole, has a low charge trap density and a long carrier lifetime, and can be well used in solar cells.

[0066] In a third aspect, the present invention provides a perovskite solar cell. The perovskite solar cell of the present invention comprises the perovskite film provided in the second aspect of the present invention.

[0067] The perovskite solar cell provided in the third aspect of the present application includes the perovskite film provided in the second aspect of the present application. Based on the advantages of the perovskite film, the perovskite solar cell of the present application has good conversion efficiency.

[0068] Specifically, the perovskite solar cell of the embodiment of the present application includes a first electrode, a second electrode and a perovskite layer located between the first electrode and the second electrode, an electron transport layer is arranged between the perovskite layer and the first electrode, and the perovskite layer is the perovskite film obtained by the above-mentioned preparation method of the embodiment of the present application.

[0069] In some embodiments, the electron transport layer may be a metal oxide or a doped metal oxide, for example, the metal oxide includes at least one of TiO2, meso-TiO2, NiOx, SnO2, ZrO2, and ZnO. Titanium dioxide and lithium-doped titanium dioxide may be used in the embodiments of the present application. The electron transport layer may be a layer of metal oxide or two stacked layers of metal oxide.

[0070] In some embodiments, the first electrode may be a transparent conductive substrate, including but not limited to the following materials: fluorine-doped tin oxide (FTO), indium-doped tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), indium-doped zinc oxide (IZO), etc. The second electrode may be a metal top electrode, such as gold, silver, copper, etc., or one or more of the conductive oxide electrodes.

[0071] The preparation method of the above-mentioned perovskite solar cell includes: 1) preparing an electron transport layer on a first electrode; 2) preparing a perovskite layer on the electron transport layer, that is, the preparation method provided in the first aspect of the embodiment of the present application can be used to prepare a perovskite film; 3) preparing a second electrode on the perovskite layer. Through this method, a smooth and dense perovskite film can be prepared on the electron transport layer, reducing the negative impact of the wettability transformation of the electron transport layer surface.

[0072] In some embodiments, a hole transport layer may be provided between the perovskite layer and the second electrode to further improve the hole transport performance of the perovskite solar cell. Specifically, the material of the hole transport layer may include 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), triphenylamine (H101) with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine (EDOT-OMeTPA), N-(4-aniline)carbazole-spirobifluorene (CzPAF-SBF), poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), etc.

[0073] The following describes the invention in conjunction with specific embodiments.

[0074] Example 1

[0075] A perovskite solar cell comprises, in sequence: an FTO glass substrate, an electron transport layer, a perovskite layer, a hole transport layer, and a top electrode. The preparation method thereof is as follows:

[0076] 1) FTO glass substrate pretreatment

[0077] The FTO glass was ultrasonically cleaned with glass cleaning solution, deionized water, and ethanol for 15 minutes respectively, then dried with a nitrogen stream and treated with UV-O3 for 20 minutes.

[0078] 2) Preparation of electron transport layer

[0079] The pretreated FTO glass substrate was placed in a culture dish: 40 mM titanium tetrachloride aqueous solution was added, and the dish was placed in a 70° C. oven for 1 hour to obtain a dense titanium dioxide layer with a thickness of 40 nm.

[0080] The substrate prepared with the dense titanium dioxide layer was rinsed and dried with water, and the titanium dioxide slurry (the particle size of the titanium dioxide particles was about 30 nm) was diluted with anhydrous alcohol at a mass ratio of 7:1, and stirred for 12 hours to form a stable suspension; the suspension was coated on the substrate with an initial rotation speed of 5000 revolutions per second (r / s), an acceleration of 1000 r / s, a spin coating time of 30 seconds, and then annealed at 500°C for half an hour to obtain a porous titanium dioxide layer with a thickness of about 200 nm.

[0081] The substrate was then placed in a culture dish, 20 mM titanium tetrachloride solution was added, and the substrate was kept in an oven at 70°C for 30 minutes. After being washed with water and blown dry, a lithium carbonate aqueous solution (2 mg / mL) was spin-coated on the substrate at a speed of 3000 r / s for 30 seconds, and then annealed at 450°C for half an hour to obtain the final electron transport layer.

[0082] 3) Preparation of perovskite layer

[0083] 3.1 Lead nitrate film: First prepare a cationic surfactant aqueous solution: dissolve dimethyldi(octadecyl)ammonium chloride in water to form a cationic surfactant aqueous solution with a concentration of 5 mg / mL; then add lead nitrate to 1 ml of the cationic surfactant aqueous solution, stir and dissolve, and filter to obtain a lead nitrate aqueous solution containing a cationic surfactant, with a lead nitrate concentration of 1.5 M. Spin coat the lead nitrate aqueous solution on the electron transport layer. The process is carried out under low temperature and low humidity conditions (RH=5%, temperature=15°C). The lead nitrate aqueous solution is dynamically spin-coated at 5000 r / s, and then baked at 100°C for 30 minutes to obtain a transparent white lead nitrate film with a thickness of about 350 nm.

[0084] 3.2 Conversion of aqueous perovskite: First, the lead nitrate film was converted into MA-based perovskite by multiple immersions. Specifically, the lead nitrate film substrate was immersed in a methylamine halide solution (containing MAI and MACl, molar ratio MAI:MACl = 4:1, solvent IPA dissolution, total concentration of 10 mg / mL) for 4 minutes, taken out and rinsed with solvent IPA, dried with nitrogen and immersed again, and this process was repeated four times. Subsequently, a solution containing a high concentration of methylamidine halide salt was prepared (containing: FAI 155 mg, MAI 15 mg, MACl 20 mg, solvent 3.2 mL IPA), and the FAI-containing solution (about 200 μL) was dynamically spin-coated on the surface of the MA-based perovskite at 3000 r / s, annealed at 150°C for 15 minutes (RH about 30-40%), and a perovskite film with a thickness of 500 nm was obtained.

[0085] Spin coating of passivation agent: Spin coating of passivation agent solution (the passivation agent is PEAI, the solvent is IPA, and the passivation agent concentration is 5 mg / mL) on the surface of the perovskite film at 5000 r / s, and then drying the solvent.

[0086] 4) Preparation of hole transport layer

[0087] 72.3 mg of Spiro-OMeTAD, 28.6 μL of 4-tert-butylpyridine, and 18.6 μL of Li-TFSI acetonitrile solution (concentration of 520 mg / mL) were added to 1 mL of chlorobenzene, stirred for 12 hours, and then spin-coated on the perovskite surface at a speed of 5000 r / s for 30 seconds to obtain a hole transport layer with a thickness of about 200 nm.

[0088] 5) Top electrode preparation

[0089] The gold electrode is evaporated to a thickness of about 80nm.

[0090] Comparative Example 1

[0091] A perovskite solar cell comprises, in sequence: an FTO glass substrate, an electron transport layer, a perovskite layer, a hole transport layer, and a top electrode. The difference between the preparation method thereof and that of Example 1 is that in the preparation of the perovskite layer, no cationic surfactant dimethyl di(octadecyl)ammonium chloride is added to the lead nitrate aqueous solution, and the rest is the same as that of Example 1.

[0092] Performance Testing

[0093] like Figure 2 As shown in the electron scanning microscope photo (SEM): the upper left figure is a microscopic picture of the lead nitrate film without adding the cationic surfactant in Example 1, and the upper right figure is a microscopic picture of the lead nitrate film with adding the cationic surfactant in Example 1. The "island-like" morphology of the cracks in the lead nitrate film is significantly reduced by the action of the cationic surfactant dimethyl di (octadecyl) ammonium chloride (DMDO in the figure). The lower left figure is a microscopic picture of the perovskite film without adding the cationic surfactant in Example 1, and the lower right figure is a microscopic picture of the perovskite film with adding the cationic surfactant in Example 1. Example 1 of the present application regulates the growth of perovskite through the template of the cationic surfactant, and finally obtains a smooth and dense surface morphology of the water-based perovskite film; in addition, there are a large number of defects at the grain boundaries in the perovskite film without adding the cationic surfactant during the preparation process of Example 1, and the introduction of the cationic surfactant in Example 1 significantly promotes the growth of the perovskite grains, and obtains a dense and smooth perovskite film with a larger grain size, and obtains a high-quality perovskite film with a low density of grain boundary defects.

[0094] like Figure 3 Shown are the steady-state fluorescence photoluminescence spectrum and transient fluorescence photoluminescence spectrum of the perovskite film. The fluorescence photoluminescence (PL) data also confirms that Example 1 can effectively reduce non-radiative recombination and extend the carrier lifetime of the perovskite film due to the reduction in defect density: from 442.47ns in Comparative Example 1 to 998.38ns in Example 1.

[0095] like Figure 4 The photovoltaic efficiency diagram of the perovskite solar cell is shown in Figure 1. Thanks to the introduction of the cationic surfactant in the lead nitrate aqueous solution, the morphology of the perovskite film is optimized and the defect density is reduced. Compared with the comparative example 1, the open circuit voltage (V OC ), fill factor (FF) and photoelectric conversion efficiency (Efficiency); wherein the photoelectric conversion efficiency is increased from 20.78% of comparative example 1 to 23.43% of embodiment 1.

[0096] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a perovskite film, characterized in that: include: preparing a divalent inorganic salt aqueous solution, wherein the divalent inorganic salt in the divalent inorganic salt aqueous solution is an inorganic salt corresponding to the divalent cation of perovskite, and the divalent inorganic salt aqueous solution contains a cationic surfactant; Processing the divalent inorganic salt aqueous solution into a film to obtain a divalent inorganic salt film; The divalent inorganic salt in the divalent inorganic salt film is converted into an organic-inorganic hybrid perovskite to obtain a perovskite film.

2. The preparation method according to claim 1, characterized in that The general chemical formula of the cationic surfactant is as follows: Wherein, R1 and R2 are straight-chain alkyl groups of 1 to 3 carbon atoms, R3 and R4 are straight-chain alkyl groups of 10 to 20 carbon atoms, and X is a halogen atom.

3. The preparation method according to claim 2, characterized in that: The surfactant includes at least one of dimethyldi(octadecyl)ammonium iodide, dimethyldi(octadecyl)ammonium bromide and dimethyldi(octadecyl)ammonium chloride.

4. The preparation method according to claim 1, characterized in that: In the divalent inorganic salt aqueous solution, the concentration of the divalent inorganic salt is 1.0-2.0 mol / L, and the concentration of the cationic surfactant is 2-8 mg / mL.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The step of treating the divalent inorganic salt aqueous solution into a film comprises: coating the divalent inorganic salt aqueous solution into a film under the conditions of relative humidity <10% and temperature <20°C, and then performing a drying treatment.

6. The preparation method according to claim 5, characterized in that: The drying process is carried out at a temperature of 80 to 100° C. and for a time of 20 to 40 minutes.

7. The preparation method according to any one of claims 1 to 4, characterized in that: The step of converting the divalent inorganic salt in the divalent inorganic salt film into an organic-inorganic hybrid perovskite comprises: firstly placing the divalent inorganic salt film in a methyl ammonium halide solution for multiple immersion treatments, and then spin-coating a solution containing a formamidine halide salt after drying for annealing treatment to obtain a formamidine-based organic-inorganic hybrid perovskite.

8. The preparation method according to claim 7, characterized in that: The following steps are involved: The methylammonium halide solution contains methylammonium iodide and methylammonium chloride in a molar ratio of (3.5-4.5):1; And / or, the solution containing formamidine halide salt contains formamidine iodide and methylammonium iodide dissolved in a molar ratio of (7-10):1; And / or, the soaking treatment time is 4 to 5 minutes each time; And / or, the annealing treatment time is 140-160°C.

9. A perovskite film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. A perovskite solar cell, characterized in that: Comprising the perovskite film as described in claim 9.

Citation Information

Cited By

  • Blade coating preparation method of perovskite solar cell using potassium hexafluorophosphate

    CN121692967A